Rui Barbosa e o ensino no Pedro II: um discurso pedagógico no Brasil oitocentista- 1880-1885 - Santos, Fabio Alves dos (2005)
This research focuses on Rui Barbosa´s participation in the educational debates during the last years of the Second Brazilian Empire (1840-1889), according to his counsels presented in 1882 about the public instruction reform established by Leôncio de Carvalho through the decree 7.247, from April 19, 1879. Although these counsels are related to all levels of education, this research analyses only the proposal to the secondary and professioal (technical, as it was called) levels. Having in mind some aspects of the current literature about the counsels and the propositions that guide the project Internacionalização Nacionalização de padrões pedagógicos e escolares do ensino secundário e profissional (Internationalization / Nationalization of scholar and pedagogical standards of the secondary and professional levels), this study intends to retake Rui Barbosa´s contribution to the configuration debate of the professional and secondary education under some aspects that have not been considered in the academic production that they were referred to. The main hypothesis goes against the idea that the counsels are a species of a pedagogical treaty , a copy of foreign ideas, without connection to the national reality. On the other hand they were presented as an illustrative text of the author´s idea of belonging to a certain political group, that was on a power dispute ahead of others, to talk and legislate about the public education in Brazil. Finally, it was noticed that the reform proposed by Rui Barbosa aimed at turning Pedro II school into a space of utilitary education for a society in a growing process of modernization.